2013
DOI: 10.9734/ajea/2013/5069
|View full text |Cite
|
Sign up to set email alerts
|

Soybean (Glycine max L) Genotype and Environment Interaction Effect on Yield and Other Related Traits

Abstract: Aims: To evaluate genetic variability of five soybean genotypes, and assess genotype × environment effect on seed yield and yield related traits. Study Design: Split-plot, replicated three times. Genotypes were fixed effect while plots (main 60 m² and subplot 12 m²) were random effects. The sub-plot consists of 4 rows 5 m long with 60 cm and 10 cm inter and intra-row spacing. A strain of Rhizobium japonicum was used for inoculation at a rate of 10 g per kg of soybean seed using a sugary solution in 2009. Inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 10 publications
4
13
0
1
Order By: Relevance
“…The improvement of soybean yield had become the problem that received the most attention in soybean production (Boerma and Specht, 2004). This study demonstrated that it was beneficial to cultivate soybeans with high yield by choosing higher plant height, more nodes of main stem, more branches, more pods, more grains, and longer growth periods, which was in accordance with previous research (Yadav et al, 2009;Luo, 2010;Aditya et al, 2011;Ngalamu et al, 2013;Islam and Rai, 2015;AbdulHamid et al, 2017;Nagarajan et al, 2017). However, the undesirable association of these yield-related traits was one of the most difficult challenges for crop breeders (Yan, 2014); for example, in this study we found that 100-grain weight was negatively correlated (P≤0.001, P≤0.01) with branches, pods, and grains (−0.31<r<−0.24).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The improvement of soybean yield had become the problem that received the most attention in soybean production (Boerma and Specht, 2004). This study demonstrated that it was beneficial to cultivate soybeans with high yield by choosing higher plant height, more nodes of main stem, more branches, more pods, more grains, and longer growth periods, which was in accordance with previous research (Yadav et al, 2009;Luo, 2010;Aditya et al, 2011;Ngalamu et al, 2013;Islam and Rai, 2015;AbdulHamid et al, 2017;Nagarajan et al, 2017). However, the undesirable association of these yield-related traits was one of the most difficult challenges for crop breeders (Yan, 2014); for example, in this study we found that 100-grain weight was negatively correlated (P≤0.001, P≤0.01) with branches, pods, and grains (−0.31<r<−0.24).…”
Section: Discussionsupporting
confidence: 88%
“…The phenotypic data were ranked by individual cases and transformed into variables obeying standard normal distribution for the statistical analysis by SPSS 19.0 software (Field, 2013). The significance of interrelationships between 14 phenotypic variables across three locations was identified using Pearson's correlation coefficients of "Performance Analytics" package in R software (Micheaux et al, 2013). The correlation coefficients were formulated as follows (Wen et al, 2012):…”
Section: Descriptive and Correlation Analysismentioning
confidence: 99%
“…Generally, late maturing genotypes were taller than medium or early maturing genotypes. These findings are consistent to Mahasi et al (2010) and Ngalamu et al (2013) who found that late maturing varieties are taller than early maturing varieties due to their genetic composition and longer period to utilize the available resources optimally.…”
Section: Plant Heightsupporting
confidence: 92%
“…The obtained results are in good agreement with those reported by Gurmu, et al (2009) and Amin (2010), who found significant genotype x environment interaction mean squares for soybean seed yield. Ngalamu et al(2013) found significant sowing date, year, genotype mean squares and significant interaction between genotype and year, genotype and sowing date and the second order interaction of genotype x year x sowing date mean squares for some soybean traits which agreed with the obtained results. Also, Hussein, et al (2006), Khalil et al(2011) andAbebe, et al (2015) reported that, significant genotype , environment and genotype x environment interaction and the environment explained higher sum of squares for the response variable seed yield of faba bean.…”
Section: The Analysis Of Variancesupporting
confidence: 88%